The cyberliterary efficacy of combinatory literature in urban cishet university students (or how to imagine a paper by programming an abstract) - Torres, Rui (2020)
Scholarly work relies upon textual stability. Authors choose their words and concepts from large paradigms that are based on associative relations. However, in order to be quoted and divulged, the syntagms that result from their choices are fixed and stable. What happens if we use combinatorics (programmability) and randomness (indeterminacy) to write an essay that is never the same, but one that is variable instead? More: what if we compose a generative and aleatory abstract pointing to papers that were never published or even imagined? For the inaugural issue of The Digital Review on "Digital Essayism," Rui Torres and Diogo Marques propose an experimental "short-form essay" that takes the shape of an outline of possible papers that were never written. Composed of a title, an abstract (with purpose, problem, methods, results, and conclusions), and a set of keywords, it will use a lexicon of e-lit theory and related concepts, suggesting digital essayism to be a performance of theory. Using poemario.js, a JavaScript lib of combinatory functions created by Rui Torres and Nuno Ferreira, we will thus propose paratexts to be recombined anew at every reading, generating multiple instantiations of possible essays. In doing so, we argue that this creative research constitutes a speculative, though self-reflexive, theorization about the limits and possibilities of using digital media to perform essayism, hence revealing its dual programmable and experimental nature.